Comparative pharmacokinetics of meloxicam oil suspension in pigs at different dosages following intramuscular administration. (October 2021) - Guo, Fanxi; Li, Ying; Yang, Dawei; Jiang, Xiangyuan; Ren, Juncai; Miao, Yingxue; Ding, Fangyi; Yu, Zugong
Abstract: This study aimed to evaluate the preliminary safety of self-developed meloxicam (MEL) oil suspension and determine the comparative pharmacokinetics of it at 0.8 and 2 mg/kg body weight (b.w.) dosages in pigs following a single intramuscular administration. Six rabbits were used for the study of preliminary safety and six healthy pigs were used for pharmacokinetics study by a crossover design in two periods. The muscle irritation results showed that both of the MEL oil suspension and the conventional injection had no significant changes at the dosage of 0.4 mg/kg b.w.. However, at the dosage of 2 mg/kg b.w., both of the self-developed MEL oil suspension and the MEL conventional injection showed mild irritation to muscle. Plasma concentrations of MEL were measured by ultra performance liquid chromatography–tandem mass spectrometry (UPLC-MS/MS). The MEL plasma concentrations were quantified up to 30 h and 72 h after intramuscular administration at the low- and high-dosage, respectively. The difference was statistically significant ( P < 0.05) between different dosages in pharmacokinetic parameters of t1/2λz, Cmax, AUC0-t, AUC0-μ, MRT, and Vd . The Cmax values of MEL were 1.92 ± 0.34 μg/ml and 3.03 ± 1.25 μg/ml at dosages of 0.8 and 2 mg/kg b.w. while the tmax values were 3.25 ± 1.04 h and 4.00 ± 1.26 h, respectively. The pharmacokinetics results of self-developed MEL oil suspension demonstrated that the retention time of it in pigs was prolonged, showing the sustained-release effect. Therefore, Oil suspension was an ideal new drug loading form of MEL. Highlights: Evaluating the muscle irritation of Meloxicam oil suspension and Meloxicam conventional injection of different dosages. Comparing the pharmacokinetics of Meloxicam oil suspension in pigs at different dosages. The difference was statistically significant ( P < 0.05) between different dosages in t1/2λz, Cmax, AUC0-t, MRT, and Vd . The AUC0- ∝ values increased in a dose-dependent manner.